Attitude as a mediator between socio-ecological factors and non-communicable disease management: a study protocol - Bakar, Azrin Shah Abu; Rahman, Haliza Abdul; Nazan, Ahmad Iqmer Nashriq Mohd (Intelektual Pustaka Media Utama, 2025)
Non-communicable diseases (NCDs) have risen in Malaysia, and people with low socioeconomic status are more vulnerable to NCDs. Previous studies on the management of non-communicable disease have focused on aspects of socioeconomic factors, individual factors, and psychosocial factors. However, there is limited information on socio-ecological factors (e.g. intrapersonal, interpersonal, organizational, community, and societal factors) and their direct and indirect effect of socio-ecological factors on non-communicable disease management mediated by attitude has not been investigated. Thus, this study aimed to investigate the role of attitude as a mediator between socio-ecological factors and non-communicable disease management among support staff in Putrajaya, Malaysia. A cross-sectional study using cluster random sampling will be conducted at selected Ministries, in Putrajaya Malaysia. The questionnaire will assess respondents’ background information, knowledge of non-communicable disease, attitude towards preventing non-communicable disease and chronic illness resources survey (CIRS) to measure socio-ecological factors. Descriptive and inferential statistics will be used in data analysis using SPSS and SEM with AMOS software. The findings will provide a theoretical model for understanding the various factors that determine towards non-communicable disease management through mediation of attitude.